A systematic review of studies on fine and coarse root traits measurement: towards the enhancement of urban forests monitoring and management - Fantozzi, Daniele; Montagnoli, Antonio; Trupiano, Dalila; Di Martino, Paolo; Scippa, Gabriella Stefania; Agosto, Gustavo; Chiatante, Donato; Sferra, Gabriella (Frontiers in Forests and Global Change, 2024)
The analysis of fine and coarse roots' functional traits has the potential to reveal the performance of the root system which is pivotal in tree growth, development, and failure in both natural and urban forest ecosystems. Also, root traits may be a powerful indicator of tree resilience mechanisms. However, due to the inherent difficulties in measuring 'the hidden half', and despite the recent advancement, the relationships among root functional traits and biotic and abiotic drivers still suffer a lack of information. Thus, our work aimed to evidence knowledge milestones and gaps and to categorize, discuss, and suggest future directions for effective experimental designs in fine and coarse root studies. To this aim, we conducted a systematic literature review supported by backward manual referencing based on 55 root functional traits and 136 plant species potentially suitable for afforestation and reforestation of natural and urban forest ecosystems. The majority of the 168 papers on fine and coarse root studies selected in our review focused predominantly on European natural contexts for a few plant species, such as Fagus sylvatica, Picea abies, Pinus sylvestris, and Pinus cembra, and root functional traits such as standing biomass, phenology production, turnover rate and non-structural carbohydrates (NSC). Additionally, the analyzed studies frequently lack information and uniformity in experimental designs, measurements, and statistical analysis highlighting the difficult integrations and comparison of outcomes derived from different experiments and sites. Moreover, no information has been detected in selected literature about the urban forest ecosystems while most of the studies are taken on natural forests. These biases observed during our literature analysis led us to give key indications for future experiment designs with fine and coarse roots involved, which may contribute to the building up of common protocols to boost the monitoring, managing, and planning of afforestation and reforestation projects.